2018
DOI: 10.1002/ls.1430
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of couple‐stress effects in gas foil bearings using the V. K. Stokes micro‐continuum theory

Abstract: This paper presents an original theoretical investigation of the steady‐state and dynamic characteristics of foil journal bearings lubricated with contaminated air taking into account couple stresses because of the presence of pollutant substances. The substance can be solid particles (eg dust, ash, pollen, and smoke). In aerodynamic lubrication theory, a fluid with couple stresses so‐called couple stress or polar fluid may be considered as one characterised by the 2 physical constants μ and η, which are the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The extension of the Stokes couple stress theory to anisotropic or non-Newtonian fluids would be especially problematic. Although the Stokes' theory requires two couple-stress viscous parameters  and  for linear isotropic fluids, it is not known why in very recent work Laouadi et al (2018) incorrectly state that this theory depends on one couple-stress viscous parameter  . As mentioned, the dependence of the velocity profile and stresses on both viscous parameters  and  is obviously seen for Poiseuille flow through circular pipes (Stokes, 1966(Stokes, , 1984.…”
Section:  22mentioning
confidence: 99%
“…The extension of the Stokes couple stress theory to anisotropic or non-Newtonian fluids would be especially problematic. Although the Stokes' theory requires two couple-stress viscous parameters  and  for linear isotropic fluids, it is not known why in very recent work Laouadi et al (2018) incorrectly state that this theory depends on one couple-stress viscous parameter  . As mentioned, the dependence of the velocity profile and stresses on both viscous parameters  and  is obviously seen for Poiseuille flow through circular pipes (Stokes, 1966(Stokes, , 1984.…”
Section:  22mentioning
confidence: 99%
“…The modified Reynolds formulas on the lubrication characteristics of journal bearing affected by magnetic fluids have been derived on the basis of Stokes micro-continuum theory, 16 considering the couple action between the rotating action of journal bearing and its oil-film squeeze dynamic action based on Hu and Xu’s theoretical research. 14 On the basis of this, the impact of the magnetic supporting oil-film pressure due to the symmetric gradient magnetic field in axial and its lubrication characteristics have been analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that adding a small amount of long-chain polymer to the lubricant can effectively improve the load capacity performance of the friction pair. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] A small amount of long-chain polymer changes the fluid characteristics of the lubricant, changing the lubricant fluid characteristics from Newtonian fluid to couple stress fluid. From the perspective of engineering applications, such measures are simple and effective.…”
Section: Introductionmentioning
confidence: 99%
“…The current couple stress fluid lubrication theory is relatively mature, and the mathematical model of couple stress fluid lubrication is derived based on Stokes' microcontinuum theory. Many scholars have applied the mathematical model of coupled stress fluid lubrication to study the static and dynamic performance of various types of friction pairs such as journal bearing, [1][2][3][4][5][6][7] porous journal bearing, 8 double-layered journal bearing, 9 two-lobe journal bearing, [10][11][12] three-lobe journal bearing, 13 gas foil bearing, 14 and sliding bearing. 15 Compared with Newtonian fluid, coupled stress fluid can effectively improve the load capacity of the friction pair.…”
Section: Introductionmentioning
confidence: 99%